The Present as Platform - Chris Ingraham (Media Theory)
Recent interest in platform studies has called attention to the ways technologies both afford and constrain creative ways of participating in social and cultural life. Digital platforms have become adept at collecting historical data and using it not just to predict future outcomes, but to produce the present through cultivated expectations of what it will have been. By exploring the case of amateur sound-recording media such as the mixtape, the writable CD, and online playlists, this paper explores how the material constraints of these media change the possibilities for what curated music can communicate. If one result is to mediate different temporal experiences by using timely music to elevate moments into events, then algorithmic music recommendations foreclose the affectability of experience by circumscribing it in advance as deliverable.